Calcium channel blockers and breast cancer incidence: An updated systematic review and meta-analysis of the evidence - Wright, Cameron; Moorin, Rachael; Chowdhury, E.; Stricker, B.; Reid, Christopher; Saunders, C.; Hughes, Jeffery (Elsevier Inc., 2017)
Controversy exists regarding the potential association between taking calcium channel blockers (CCBs) and the development of breast cancer. As a positive association would have important public health implications due to the widespread use of CCBs, this study aimed to incorporate new evidence to determine whether an association is likely to exist. We searched MEDLINE, EMBASE and the Cochrane Library to 28 June 2016 for relevant literature. References and citing articles were checked and authors contacted as necessary. Two authors independently selected articles and extracted data. Twenty-nine studies were reviewed; 26 were non-randomised studies (NRS). Meta-analysis of study data where adjustment for ‘confounding by indication’ was judged to be present suggests that an association, if any, is likely to be modest in magnitude (pooled odds/risk ratio 1.09 (95% confidence interval (CI) 1.03–1.15, I 2 = 0%, 8 sub-studies; pooled hazard ratio 0.99 (95% CI 0.94–1.03, I 2 = 35%, 9 sub-studies)). There are credible study data showing an increased relative risk with long-term use of CCBs, but the results of our meta-analysis and of meta-regression of log relative risk against minimum follow-up time are mixed. The current summative evidence does not support a clear association between taking CCBs and developing breast cancer. However, uncertainty remains, especially for long-term use and any association might not be uniform between different populations and/or breast cancer sub-types. We t hus recommend further NRS in settings where CCB use is highly prevalent and population-based cancer, prescription and health-registries exist, to resolve this continuing uncertainty. PROSPERO, CRD42015026712.